Vehicle-to-Vehicle (V2V) Communications ‘Overview - Michal VARMUS; Gabriel KOMAN; Katarína ZÁBOVSKÁ; Boris BUČKO (Communications of International Proceedings, 2021)
In recent years, there have been proposed many different Vehicle-to-Vehicle (V2V) communication models, that are utilizing new technologies, or are using mathematics to optimize the systems. This paper review some of the proposed solutions, such as the usage of the free TV White Space (TVWS), Visible Light Communication (VLC), or the LTE based communication optimization by the pricing-based interference management scheme. Also, some of the subject related basic theory overview is included in the paper (such as the general wireless communication technologies used in ITS), as well as the related potential benefits are discussed. It is important to review different solutions to create a uniform overview, since it could help in the future attempts of various models integration.
Keywords: Electromobility; V2V; ITS; Communication Technology; Communication Model; LTE